Analysis of corruption risk and prevention efforts based on the perceptions of public service users in Merauke Regency - Beatus Tambaip; Dina Fitri Septarini; Fitriani Fitriani; Ransta L. Lekatompessy (Komisi Pemberantasan Korupsi, 2025)
Corruption in local government in Indonesia, particularly in Merauke Regency, South Papua Province, undermines public trust and development. This study maps corruption risks from the perspective of service users, measures the impact of prevention, and develops recommendations through the 2024 KPK SPI, integrating Principal-Agent, Institutional, Collective Action, and Social Capital theories. Method: Quantitative (191 external respondents in 63 OPDs via CAPI), validated qualitatively (interviews with 9 key informants). Results: SPI score of 65.16 (highest in South Papua, national average), zero prevalence of corruption. Structural-geographical risks in remote districts (information asymmetry, unequal access, weak supervision). Positive (70% improvement) but asymmetrical impact of prevention measures (Integrity Zone, MCP, e-procurement). Recommendations from this study include the establishment of mobile Integrated Service Posts, community supervision, inclusive digitalization, and local culture training. Contribution: A bottom-up prevention model for WBK/WBBM and data-driven autonomous governance reform.